2015
DOI: 10.3390/nano5042203
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Ultrasmall Pt Nanoparticles as Highly Active Electrocatalysts for Methanol Oxidation

Abstract: Ultrasmall nanoparticles, with sizes in the 1–3 nm range, exhibit unique properties distinct from those of free molecules and larger-sized nanoparticles. Demonstrating that the hydrothermal method can serve as a facile method for the synthesis of platinum nanoparticles, we successfully synthesized ultrasmall Pt nanoparticles with an average size of 2.45 nm, with the aid of poly(vinyl pyrrolidone) (PVP) as reducing agents and capping agents. Because of the size effect, these ultrasmall Pt nanoparticles exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The nanoparticles were synthetized using H 2 PtCl 6 .6H 2 O as Pt precursor and PVP as stabilizer The procedure was adapted from refs. [36, 37, 38], and is described in Supporting Information (section 2). Prior to their use in the MOF synthesis, Pt nanoparticles (Pt‐NPs) were characterized in depth (section 2 in Supporting Information), and TEM observations evidenced that the Pt nanoparticles possess an average diameter of 3.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The nanoparticles were synthetized using H 2 PtCl 6 .6H 2 O as Pt precursor and PVP as stabilizer The procedure was adapted from refs. [36, 37, 38], and is described in Supporting Information (section 2). Prior to their use in the MOF synthesis, Pt nanoparticles (Pt‐NPs) were characterized in depth (section 2 in Supporting Information), and TEM observations evidenced that the Pt nanoparticles possess an average diameter of 3.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…50 Another approach is via hydrothermal reactions, which use high pressure and temperature in addition to water and the organic compound to obtain metallic NPs. 51,52 Different materials have been reported to work, such as platinum 53 or titanium oxide 54 NPs for the catalytic industry, and Te, a rare metalloid, is also considered a good candidate. 55,56 Te nanowires (TeNWs) have been synthesized by employing hydrothermal reactions mainly for semiconductor and catalytic applications; 57,58 however, their biomedical applications are largely unknown, as Te -even has similarities with oxygen, selenium, or sulfuris not a trace element, and it has not been considered for biochemical interests.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological studies displayed well-dispersed spherical nanoparticles with uniform size distribution and an average particle diameter of 2–7 nm ( Figure 7 a) [ 123 ]. Similarly, ultra-small Pt-NPs were produced using hydrothermal [ 124 ] and water-in-oil microemulsion [ 125 ] techniques that resulted in narrow size distribution and average diameters of 2.45 ( Figure 7 c) and 5 nm ( Figure 7 d), respectively. The studies revealed well-defined crystal lattice planes with clusters containing a mixture of irregular and spherical morphologies.…”
Section: Green Synthesis Of Transitional Metals and Their Oxidesmentioning
confidence: 99%